Evaluation of Some Fungicides and Bio-Agents against Sclerotium rolfsii and Foot and Root Rot Disease of Eggplant (Solanum melongena L.) - Nuray Alam Siddique, Mohammad; Noman Faruq Ahmmed, Abu; Golam Hasan Mazumder, Md.; Khaiyam, M O; Rafiqul Islam, Md. (The Agriculturists, 2016)
Two experiments were conducted in a complete randomized design (CRD) with three replications to evaluate the efficacy of some fungicides and bio-agents against foot and root rot of eggplant. Ten treatments including five fungicides, two plant extracts, one poultry manure and an antagonist were evaluated against the disease and its causal agent. Fungicides and plant extracts were sprayed at the base of each plant and adjacent soil at 40, 50 and 60 days after transplanting (DAT). Poultry manure and bio-agent were applied to the soil before transplanting. The highest reduction of mycelium growth (74.44 %) and sclerotia production (77.13 %) were recorded in Bavistin 50 WP by poison food technique. Topgan 50 WP and Ridomil Gold also had similar effects. The lowest incidence (7.10 %) of foot rot was observed in Bavistin 50 WP at 120 DAT that was similar with Topgan 50 WP and Ridomil Gold. The lowest disease severity (stem lesion area) was also found in each of Bavistin 50 WP (0.71 cm) and Topgan 50 WP which resulted in higher yield (18.07 ton/ha). Application of bio-agent (Trichoderma harzianum) also showed promising effect against foot and root rot disease. Bavistin 50 WP is therefore recommended for controlling the foot and root rot of eggplant. The Agriculturists 2016; 14(1) 92-97